The Potential Protective Role of Vitamin D Supplementation on HIV-1 Infection - Alvarez, Natalia; Aguilar-Jimenez, Wbeimar; Rugeles, Maria T. (Frontiers in Immunology, 2019)
HIV infection remains a global and public health issue with the incidence increasing in some countries. Despite the fact that combination antiretroviral therapy (cART) has decreased mortality and increased the life expectancy of HIV-infected individuals, non-AIDS conditions, mainly those associated with a persistent inflammatory state, have emerged as important causes of morbidity and mortality despite effective antiviral therapy. One of the most common comorbidities in HIV-1 patients is Vitamin D (VitD) insufficiency, as VitD is a hormone that, in addition to its physiological role in mineral metabolism, has pleiotropic effects on immune regulation. Several reports have shown that VitD levels decrease during HIV disease progression and correlate with decreased survival rates, highlighting the importance of VitD supplementation during infection. An extensive review of 29 clinical studies of VitD supplementation in HIV-infected patients showed that regardless of cART, when VitD levels were increased to normal ranges, there was a decrease in inflammation, markers associated with bone turnover, and the risk of secondary hyperparathyroidism while the anti-bacterial response was increased. Additionally, in 3 of 7 studies, VitD supplementation led to an increase in CD4+ T cell count, although its effect on viral load was inconclusive since most patients were on cART. Similarly, previous evidence from our laboratory has shown that VitD can reduce the infection of CD4+ T cells in vitro. The effect of VitD supplementation on other HIV-associated conditions, such as cardiovascular diseases, dyslipidemia or hypertension, warrants further exploration. Currently, the available evidence suggests that there is a potential role for VitD supplementation in people living with HIV-1, however, comprehensive studies are required to define an adequate supplementation protocol for these individuals.